Exploration Of Paylater Usage Behavior And Its Implications For Financial Distress Vulnerability Among University Students - Nisa Septiani; Wati Rahayu; Iwan Setiawan (POLITEKNIK LP3I, 2026)
This study aims to explore the behavior of Buy Now Pay Later (BNPL) usage and its implications for Financial Distress among university students. A qualitative exploratory approach was employed to gain an in-depth understanding of students’ financial behavior in the context of digital credit. Data were collected through semi-structured in-depth interviews with students who actively use paylater services and analyzed using thematic analysis. The findings indicate that paylater usage is largely driven by consumptive needs, supported by ease of access, payment flexibility, and lifestyle influences. Students often perceive paylater as a practical financial solution; however, they tend to exhibit overconfidence in their future repayment capacity. This leads to less prudent financial decisions and increases the risk of financial imbalance. The study also finds that such behavior may result in Financial Distress, reflected in cash flow difficulties, delayed payments, and rising financial pressure. Nevertheless, the level of vulnerability varies depending on individual factors such as financial literacy, self-control, and social environment. The study concludes that paylater usage is not merely a financial tool but a behavioral phenomenon. Strengthening financial literacy and self-control is therefore essential to mitigate Financial Distress risks among students.